Selective laser sintering of polyamide 12/flame retardant compositions. (November 2020) - Batistella, Marcos; Regazzi, Arnaud; Pucci, Monica Francesca; Lopez-Cuesta, José-Marie; Kadri, Ouassila; Bordeaux, David; Ayme, Florence
Highlights: Flame retardants and mineral fillers were evaluated to fire retard polyamide 12 by SLS. Flame retardants impacts SLS processability of compositions depending on FR type. Interactions between flame retardants and mineral fillers were observed. Best results were obtained for flame retardant/mineral filler compositions. Abstract: In this work, various flame retardants (FR) and clays were added to polyamide 12 (PA12). The processability by Selective Laser Sintering (SLS), thermal behaviour and flame retardancy of these compounds were evaluated. The observations show an important impact on powder flowability of some formulations containing melamine cyanurate and melamine polyphosphate leading to difficulties during SLS process. The incorporation of FRs also leads to changes in melting and crystallization temperatures of polyamide as a function of the FR type. Furthermore, in order to evaluate the influence of the process on thermal properties of samples, a comparison between thermocompression (TC) and SLS techniques was performed for the formulations containing the flame retardants alone. The addition of flame retardants impacts the porosity of the SLS samples as a function of the FR type. For the additives which are able to melt during SLS process, a lower porosity was observed. Samples made by TC containing 30 wt% of ammonium polyphosphate, zinc diethylphosphinate and a pentaerythritol ester of methane phosphonic acid showed a better thermal stability and flame retardancy compared to the ones made by SLS, probably due to the porosity of the SLS samples and some degradation of the flame retardant by the laser beam. For the formulation containing only zinc borate, no difference was observed between TC and SLS. In order to evaluate possibly synergistic effects between flame retardants, binary and ternary formulations were prepared by SLS. On the whole, these formulations led to an improvement of flame retardancy compared to neat PA12. Moreover, XRD results showed the formation of borophosphates for binary and ternary formulations, indicating interactions between flame retardants. EDX results showed that at least 95% of the phosphorus remained in the residue for the formulations containing zinc borate, thus corroborating the results obtained by XRD. The partial substitution of zinc borate by kaolinite led to a further improvement of flame retardancy at the expense of a porosity increase in the samples.